1992
DOI: 10.1103/physrevb.46.11840
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric power of theBi2Sr2et al.

Abstract: The temperature dependence of the thermoelectric power (TEP) of Bi2Sr,Ca 1 Y Cu&08+y samples are reported for x =0-0.9 in the temperature range 77 -300 K. TEP is positive and large for large x and decreases with decreasing x (increasing carrier concentration). TEP is negative for the x =0 sample.The results are discussed following strong correlation and the Nagaosa and Lee model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…Eq. (7) was fitted the TEP data obtained by some research groups very well (Sita and Singh, 1998;Wang et al, 1996;Mandal et al, 1992;Singh and Sita, 1999). The fit of Eq.…”
Section: Two-band Model With Linear T-termmentioning
confidence: 99%
See 1 more Smart Citation
“…Eq. (7) was fitted the TEP data obtained by some research groups very well (Sita and Singh, 1998;Wang et al, 1996;Mandal et al, 1992;Singh and Sita, 1999). The fit of Eq.…”
Section: Two-band Model With Linear T-termmentioning
confidence: 99%
“…However, the suppression of the superconductivity in the V-substituted Bi-2223 system was ascribed to a decrease of the carrier concentration (Nkum, 1998 Many studies have been done on the Pr-substitution for Ca in the Bi-based HT c system (Sun et al, 1998a(Sun et al, , 1998bChen et al, 1994;Li et al, 2000aLi et al, , 2000bLi et al, , 2000cdos Santos et al, 2001). However, there is no study on the Pr-substitution for Cu in the BSCCO HT c materials in literature.…”
Section: Introductionmentioning
confidence: 96%
“…Compared to resistivity and Hall coefficient measurements, measurement of Seebeck coefficient is a powerful technique in probing the transport phenomena with minimal distortion arising from the defect structures, etc., which are not the characteristic of the sample studied. Several authors have reported Seebeck coefficients for several systems such as La 2Ϫx (Sr,Ba) x CuO 4 , 13,14 YBa 2 Cu 3 O 7Ϫ␦ ͑YBCO͒, 10,12,[15][16][17] Bi 2 Sr 2 Ca 1 Cu 2 O 8ϩy , [18][19][20] Tl 2 Ba 2 Ca 2 Cu 3 O y , 21,22 and HgBa 2 Ca 2 Cu 3 O 8ϩ␦ system, 23,24 and have analyzed the results obtained in the light of energy band calculations to understand the transport mechanism involved. 10,12,25,27 One of the established consensus on the YBa 2 Cu 3 O 7Ϫ␦ system is that the Cu 3d and O 2p orbitals in the vicinity of the Fermi energy (E f ) constitute the superconductivity in this system.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported on Bi 2 Sr 2 Ca 1−x R x Cu 2 O y (Bi-2212) system (R = Rare-earth). [1][2][3][4][5][6][7][8][9][10][11] Some of these reports include the effect of substitution of Ca by rare-earth element on the TEP of Bi 2 Sr 2 CaCu 2 O y (Bi-2212) phase. 1,2,10,11 The TEP measurements on other cuprate superconducting systems, viz.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Some of these reports include the effect of substitution of Ca by rare-earth element on the TEP of Bi 2 Sr 2 CaCu 2 O y (Bi-2212) phase. 1,2,10,11 The TEP measurements on other cuprate superconducting systems, viz. La-, [13][14][15][16][17][18][19] Y-, [19][20][21][22][23][24][25][26][27][28][29][30] Bi-, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Tl-33, …”
Section: Introductionmentioning
confidence: 99%